Fatigue analysis of water intake risers: Hydrodynamic damping effect and a hybrid frequency-time domain method. (January 2021) - Gao, Zhenguo; Efthymiou, Mike; Cheng, Liang; Zhou, Tongming; Minguez, Matthieu; Zhao, Wenhua
Abstract: The fatigue performance is key to the design of water intake risers (WIRs), which is a novel concept used to convey cooling water for liquefaction of natural gas at sea. To estimate the fatigue life, it is crucial to accurately predict the response amplitude of the WIRs, which is dominated by hydrodynamic damping. In operational conditions, the motion amplitudes of WIRs are usually smaller than their diameter, and thus leading to a flow regime of KC  < 5. It is found in this flow regime; the hydrodynamic damping largely depends on the motion magnitude of the risers. To consider this coupling effect, a hybrid frequency-time domain fatigue analysis method is proposed, where a nonlinear stress transfer function is adopted. The hybrid method accounts for the coupling effect between the hydrodynamic damping and the structural motion. Significantly reducing the computational cost, this method provides results as accurate as that from a time domain analysis based on the relative velocity model with a constant drag coefficient. Furthermore, recommendations for further simplification of the fatigue analysis recognizing the coupling effect are given. Highlights: The coupling effect of drag coeffient and the structure motion at low KC flow regime is investigated. A hybrid frequency-time domain model is proposed for fatigue analysis. The coupling effect is considered when calculating nonlinear stress transfer functions. A constant drag coefficient method is recommended, significantly reducing computational efforts.